A comparison of pollen grains of Potentilla recta L. (Rosaceae) groups A, B & C in Turkey - Köksal, Ela Ayse; Asci, Baris; Pinar, Nur Münevver (Bangladesh Journal of Plant Taxonomy, 2010)
Not available.